A new approach to mathematics learning K–12 in Turkey - (:unkn) unknown (Taylor and Francis, 2015)
Information technologies have become a very big part of our lives in the past decade, including in academic life. The effective strategies that have been proven to be useful during and after mathematics classes, such as teacher lectures, group work, class exercises, and students’ social interactions, can be enhanced by the use of these new technologies, notably by mobile technologies. We have observed that in many high schools and colleges these new technologies have begun to spread and to be used in varying ways. In this chapter we would like to share our experiences in mobile learning in mathematics in a high school tenth-grade pre-calculus course in Turkey. © 2016 Taylor & Francis. All rights reserved.